Genetic Diversity and Genetic Differentiation of Populations of Golden-Backed Carp (Cyprinus carpio var. Jinbei) in Traditional Rice Fields in Guizhou, China - Da Ji; Xin Su; Junjie Yao; Wenzheng Zhang; Rongrong Wang; Shuhai Zhang (Animals, 2022)
The aim of this study was to assess the current status of the germplasm resources of golden-backed carp (Cyprinus carpio var. Jinbei) cultured in paddy fields in Guizhou Province, China. Five populations of golden-backed carp in Liping County, Jinping County, Huangping County, Congjiang County and Duyun City in Guizhou Province were subjected to high-throughput sequencing by 2b-RAD technology, and their genetic diversity and genetic differentiation were analysed. Based on sequencing, 44,896 SNP loci were obtained, and all five population genetic diversity indicators showed low diversity. In the NJ tree, the Congjiang and Liping populations were mixed together, and the other three groups formed a cluster. A cross-validation error box plot and pong cluster plot were constructed to show the K value results. When K = 1, the cross-validation error rate was the lowest. Principal component analysis showed that the Duyun population formed a group separate from the group comprising the other four populations. The genetic differentiation index and genetic distances between the Duyun population and the remaining four populations were greater than 0.05, indicating population differentiation. The genetic diversity of the five populations of golden-backed carp in Guizhou Province was low, the genetic differentiation of the Duyun population was the most significant, and the Duyun population was separate from the other four groups.